PENGARUH PENERAPAN SISTEM INFORMASI AKUNTANSI, PENGENDALIAN INTERN DAN PENGGUNAAN TEKNOLOGI INFORMASI AKUNTANSI TERHADAP KINERJA KARYAWAN - Fathul Hilal Perdanakusuma; dandi simanjorang (Jurnal Ilmu Akuntansi, 2021)
The purpose of this study was to determine the effect of the application of accounting information systems, internal control and the use of accounting information technology partially or simultaneously on the performance of employees at PT. Double Prestige. This study uses primary data through questionnaires distributed to respondents PT. Double Prestige. The number of samples taken as many as 69 employees of PT. Double Prestige. The sampling technique used purposive sampling method. Data were analyzed by multiple linear regression method. Based on the results of the study, it shows that the application of accounting information systems has no significant effect on employee performance, internal control has a significant effect on employee performance, the use of accounting information technology has no significant effect on employee performance. Simultaneously the application of accounting information systems, internal control and the use of accounting information technology have a significant effect on employee performance at PT. Double Prestige.